2008
DOI: 10.1002/qj.260
|View full text |Cite
|
Sign up to set email alerts
|

The life cycle of convective‐shower cells under post‐frontal conditions

Abstract: Seventeen days with post-frontal shower precipitation are analysed by means of radar data obtained from the German Weather Service's C-band radar network. The life cycle of clusters -defined here as contiguous rain areas including one or more radar-reflectivity peaks (i.e. convection cells) -is investigated. To allow for the continuous tracking of clusters, sometimes over a time period of more than an hour, a new, specially adapted tracking algorithm has been developed. The life cycle of convective clusters co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…It is equivalent to a relatively high time resolution that might be available in the data from current operational radar networks (e.g. Weusthoff and Hauf, 2008a). We have checked that our conclusions are not qualitatively affected by reasonable changes of this choice.…”
Section: The Role Of Events Within the Lifecyclementioning
confidence: 96%
See 1 more Smart Citation
“…It is equivalent to a relatively high time resolution that might be available in the data from current operational radar networks (e.g. Weusthoff and Hauf, 2008a). We have checked that our conclusions are not qualitatively affected by reasonable changes of this choice.…”
Section: The Role Of Events Within the Lifecyclementioning
confidence: 96%
“…The existence of such pulses may complicate the careful tracking of cumulus clouds because identification criteria that pickout individual thermals are liable to pick-out objects that are subject to various interactions. Those interactions may be difficult to describe even qualitatively (Westcott, 1984) but both cell-merging (Wiggert et al, 1981;Weusthoff and Hauf, 2008a) and cell-splitting (Fujita et al, 1975) have been observed to be common phenomena. One of the goals here then is to develop a tracking system that is robust but detailed enough to deal with situations in which interactions between the tracked objects are commonplace.…”
Section: Statistical Investigations Into the Lifecycles Of Cumulus CLmentioning
confidence: 99%
“…The analysis of surfacerainfall features, including tracking their life cycles, has previously been used to understand model errors in representing convection (e.g., Weusthoff and Hauf 2008;Varble et al 2011;Caine et al 2013;Clark et al 2014). In their study of multiple DYMECS cases, 2014) jointly analyzed storm-averaged rainfall rate and area and noted that although 500-and 200-m grid-length simulations generate a similar number of small storms to radar observations, these small storms tend to have rainfall rates a factor of 2 too high.…”
Section: Storm Life Cyclesmentioning
confidence: 99%
“…Such cluster analysis of convective cloud systems has been described previously, however much of this work has made use of satellite data, with a focus on tropical convection and thunderstorms. Only a little work has used cell tracking to examine the behaviour of precipitating cumulus clouds (Weusthoff and Hauf 2008a; Weusthoff and Hauf 2008b; Tadesse and Anagnostou 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For the identification of cells, their work also used satellite imagery, which has a lower temporal resolution than the radar data examined for this case. The life cycle of convective showers following a cold front was examined by Weusthoff and Hauf (2008a), Weusthoff and Hauf (2008b); this analysis was done using radar data, and used a tracking algorithm to follow cells of high rain‐rate. The growth and decay of these cells was described with respect to the number of rain‐rate maxima within each cluster, and it was found that over the course of their lifetime the clusters go through five stages: genesis, growth, stagnation, decay and dissolution.…”
Section: Introductionmentioning
confidence: 99%